Derivations and Deformations of δ-Jordan Lie Supertriple Systems - Shengxiang Wang; Xiaohui Zhang; Shuangjian Guo (Advances in Mathematical Physics)
Let T be a δ-Jordan Lie supertriple system. We first introduce the notions of generalized derivations and representations of T and present some properties. Also, we study the low-dimensional cohomology and the coboundary operator of T, and then we investigate the deformations and Nijenhuis operators of T by choosing some suitable cohomologies.